Confiabilidad y consistencia interna de la versión en español para Colombia del Índice de Western Ontario para Manguito Rotador (WORC) - Martínez Cano, Juan Pablo (2018)
Background: The Western Ontario Rotator Cuff Index (WORC) is an assessment tool developed to evaluate quality of life in patients with rotator cuff disease (RCD). The purpose of this study is to translate the WORC index into Spanish and to evaluate its reproducibility and internal consistency in patients with RCD. Methods: Following guidelines from literature, the WORC index was translated. Sixty patients with RCD were asked to complete the questionnaire. To evaluate reliability, they were asked to answer it for a second time within the next 14 days. The Cronbach’s α (CA) and the intraclass correlation coefficient (ICC) were calculated to determine test-retest reliability and internal consistency. Bland-Altman plot and reliable change index (RCI) were used to evaluate measurement error. Results: Cronbach’s α was 0.96 for the total WORC score (ranges 0.85-0.94 for the five domains).Excellent test-retest reliability was seen with an ICC of 0.98, with the domains ranging between 0.91-0.97. The Bland-Altman plot showed no systematic differences, and the RCI for the total WORC index was 7.6%. Conclusion: The Spanish version of the WORC index is a valid and reliable tool for evaluating quality of life in patients with RCD and may be used in Spanish speaking countries like Colombia. Level of evidence: Basic Science Study, Development or Validation of Outcomes Instruments/Classification Systems.